Analysis of the interactions of sulfur‐containing amino acids in membrane proteins. (8th June 2016) - Gómez‐Tamayo, José C.; Cordomí, Arnau; Olivella, Mireia; Mayol, Eduardo; Fourmy, Daniel; Pardo, Leonardo
Abstract: The interactions of Met and Cys with other amino acid side chains have received little attention, in contrast to aromatic–aromatic, aromatic–aliphatic or/and aliphatic–aliphatic interactions. Precisely, these are the only amino acids that contain a sulfur atom, which is highly polarizable and, thus, likely to participate in strong Van der Waals interactions. Analysis of the interactions present in membrane protein crystal structures, together with the characterization of their strength in small‐molecule model systems at the ab‐initio level, predicts that Met–Met interactions are stronger than Met–Cys ≈ Met–Phe ≈ Cys–Phe interactions, stronger than Phe–Phe ≈ Phe–Leu interactions, stronger than the Met–Leu interaction, and stronger than Leu–Leu ≈ Cys–Leu interactions. These results show that sulfur‐containing amino acids form stronger interactions than aromatic or aliphatic amino acids. Thus, these amino acids may provide additional driving forces for maintaining the 3D structure of membrane proteins and may provide functional specificity.